2014
DOI: 10.1093/jac/dku427
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of 6-quinolinyl N-oxide chalcones against Paracoccidioides

Abstract: The results presented in this paper confirm the antifungal potential of the chalcones tested. The chalcone 4c was the more effective at controlling the disease in mice and this compound could be a candidate for future studies of the treatment of paracoccidioidomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The efficiency of CP1 in reducing the lung fungal burden was very similar to that of treatment with ITZ, but the host inflammatory response was better controlled in the animals treated with CP1. Similar results were found with treatment with chalcone (compound 4c), which presented pulmonary parenchyma preserved with mild areas of inflammation (31). Although ITZ is an oral drug with good activity against P. brasiliensis, it leads to important adverse reactions (33).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The efficiency of CP1 in reducing the lung fungal burden was very similar to that of treatment with ITZ, but the host inflammatory response was better controlled in the animals treated with CP1. Similar results were found with treatment with chalcone (compound 4c), which presented pulmonary parenchyma preserved with mild areas of inflammation (31). Although ITZ is an oral drug with good activity against P. brasiliensis, it leads to important adverse reactions (33).…”
Section: Discussionsupporting
confidence: 68%
“…Finally, the antifungal activity of a synthetic compound derived from chalcones was analyzed. This 6-quinolinyl N-oxide could inhibit the growth of many Paracoccidioides isolates, with a MIC of 5.9 mg/liter against Pb18 (31). In comparison with these recent reports, the MIC determined for CP1 (2 mg/liter) against P. brasiliensis isolate Pb18 indicates superior antifungal activity, encouraging future efforts to target CS.…”
Section: Discussionmentioning
confidence: 67%
“…The 6-quinolinyl and quinolinyl N-oxide chalcones, specifically those named 4c and 4e, presented strong activity against P. brasiliensis. Histopathological analysis and a progression score of the disease in mice showed that the 4c compound was able to control inflammation and resolved the infection with better results than treatment with Itraconazole and 4e, while avoiding granuloma formation and preservation of lung tissue ( de Sá et al, 2015 ).…”
Section: Facing the Problem: Through The Diagnostic To Treatment Of Pmentioning
confidence: 99%
“…Other works have identified molecules showing more promising results; for instance, a derivative of 6-quinolinyl N-oxide chalcones showed antifungal activity similar to that of itraconazole in in vivo tests in mice, obtaining an MIC 50 and an MIC 90 of 7.8 and 23.4 g · ml Ϫ1 , respectively (40). Itraconazole inhibits the fungus-mediated synthesis of ergosterol via inhibition of the enzyme lanosterol 14␣-demethylase in a way that alters the permeability of the fungal cell membrane.…”
Section: Fig 4 In Vitro Cytotoxicity For Hela Cells Compounds Hs1 (Amentioning
confidence: 99%